Sirach and its contexts: the pursuit of wisdom and human flourishing - Adams, Samuel L.; Goering, Greg Schmidt; Goff, Matthew J. (Journal for the study of Judaism, 2021)
List of Illustrations, Figures and Tables -- Abbreviations -- 1 Introduction: Sirach and Its Contexts -- Greg Schmidt Goering -- Part 1: The Wisdom of Ben Sira: Contexts, Categories, and Approaches -- 2 Wisdom as Genre and as Tradition in the Book of Sirach -- John J. Collins -- 3 Wisdom in Transmission: Rethinking Sirach and Proverbs -- Jacqueline Vayntrub -- 4 Appearance versus Reality and the Personification of Wisdom: Sirach's Place in the Early Jewish Sapiential Tradition -- Bradley C. Gregory -- 5 Ben Sira's Tour of the Cosmos: Sir 42:15-43:33 as Ekphrastic Wisdom -- A. Jordan Schmidt -- Part 2: The Hebrew Manuscripts of Sirach: Diversity, Continuity, and Transmission -- 6 Sirach MS C Revisited -- Frank Ueberschaer -- 7 Vav and Yod in the Hebrew Manuscripts A and B of Sirach -- Eric D. Reymond -- 8 Doublets in the Hebrew Manuscript B of Sirach -- Jean-Sébastien Rey -- Part 3: Sages and Their Contexts: Hellenism, Hymns, and Pedagogy -- 9 Where Is Ezra? Ben Sira's Surprising Omission and the Selective Presentation in the Praise of the Ancestors -- Samuel L. Adams -- 10 Sages as Singers in Sirach and the Second Temple Period -- David A. Skelton -- 11 Sirach and Imperial History: A Reassessment -- James K. Aitken -- Part 4: The Reception of the Book and Figure of Ben Sira in Antiquity and the Middle Ages -- 12 Ben Sira's Pseudo-Pseudepigraphy: Idealizations from Antiquity to the Early Middle Ages -- Benjamin G. Wright III and Eva Mroczek -- 13 The Act of Reading Ben Sira as a Generative Context for Jewish Liturgical Poetry and the Book of Ben Sira Itself -- Matthew Goff -- 14 Ben Sira in Ethiopia: The Andǝmta Commentary on Sirach 1 and 24 -- Yonatan Binyam -- Index of Ancient Sources -- Index of Modern Authors.